2006
DOI: 10.1002/dmrr.608
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity in subjects with type 1 diabetes mellitus in eu- and hyperglycaemia

Abstract: In subjects with type 1 diabetes, exercise capacity is not influenced by hyperglycaemia. Comparable levels of lactate and similar respiratory exchange ratio suggest that an increase in extracellular glucose availability did not translate into increased intracellular glucose oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
5
25
1
Order By: Relevance
“…Similar GLUox values (and the contribution to total energy yield) were also observed between the controls and diabetic patients during shorter aerobic exercises (≤ 1-h duration) [31,41]. Indeed, increased extracellular glucose availability, does not translate into increased intracellular GLUox [37,40]. At variance, T1DM patients exercising under high insulin infusion rates showed a slightly increased whole-body CHO oxidation rate [39].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Similar GLUox values (and the contribution to total energy yield) were also observed between the controls and diabetic patients during shorter aerobic exercises (≤ 1-h duration) [31,41]. Indeed, increased extracellular glucose availability, does not translate into increased intracellular GLUox [37,40]. At variance, T1DM patients exercising under high insulin infusion rates showed a slightly increased whole-body CHO oxidation rate [39].…”
Section: Discussionsupporting
confidence: 50%
“…The keystone of the algorithm is the estimate of the amount of CHO oxidized during the effort on the basis of heart rate (HR), taken as an index of exercise intensity [36]. The fuel oxidation rates during exercise were studied in T1DM patients mainly under constant insulin infusion rate and quite constant glycemia [14,[37][38][39][40]. Undoubtedly, these experimental protocols allow to carefully control several parameters that are likely to affect metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an experimentation similar to the present one [33] showed that the whole-body carbohydrates oxidation rate was not significantly different between patients with type 1 DM receiving appropriate amounts of fruit fudge (to avoid an excessive fall of glycemia) and the control group, who was not given carbohydrates during the exercise. In addition, it was reported by others that increased extracellular glucose availability does not necessarily translate into increased intracellular glucose oxidation during exercise [34], [35]. Furthermore, Chokkalingam et al [36] observed that only patients exercising under high insulin infusion rates showed a slightly increased whole-body carbohydrates oxidation rate.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, little is known on the complementary impact of differing levels of blood glucose on fuel metabolism and exercise performance in these patients. Recently, we found the contribution of carbohydrate and lipid oxidation to overall energy consumption to be similar in euglycaemia and hyperglycaemia during exercise up to 40 min, but the study design did not allow a detailed quantification of substrate fluxes [8]. Even less is known on the effect of differing glycaemic levels on fuel metabolism during aerobic exercise of longer duration in patients with type 1 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%